Protocolos de remoção química de resíduos de cimento endodôntico na dentina: influência sobre formação de camada híbrida e resistência de união a sistemas adesivos - Guiotti, Flávia Angelica [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate the cleaning capacity of the dentin surface, contaminated by a endodontic sealer containing epoxy resin (AH Plus), provided by ethanol or by xylene and its effects on the interface dentin / dentin adhesive system, by evaluating the formation of the hybrid layer and the bond strength of Scotchbond Universal (3M ESPE), immediately or after 7 days of dentin cleaning and, assessing the formation of the hybrid layer and the bond strength of Adper Scotchbond Multi Purpose (3M ESPE), immediately after cleaning the dentin surface impregnated with the sealer. Besides, compare the effects of cleaning substance (95% ethanol or xylene) and the etching time with phosphoric acid at 37% (immediately or after 7 days) to obtain open dentinal tubules and to evaluate the residues persistence of a sealer-based epoxy resin (AH Plus) on the dentin surface. In Chapter 1, dentin fragments of bovine incisors were treated with root canal irrigation, impregnated with sealer and divided into 4 groups (n = 10): G1 (EIDE), ethanol 95.0% - DE immediate; G2 (XIDE), xylene - DE immediate; G3 (EPDE), ethanol 95.0% - DE after 7 days and G4 (XPDE), xylene - DE after 7 days. After obtaining the SEM pictures (500X), the open dentinal tubules counts were performed using Photoshop CS5 program. Another 40 fragments were also prepared and also obtained SEM pictures (500X) for evaluating the persistence of sealer residues in the dentin using scores. The count of open dentinal tubules was analyzed with ANOVA and Tukey tests (P = 0.05) and the persistence of residues with the Kruskal Wallis and Dunn tests (P = 0.05). The cleaning protocol with xylol and etching after 7 days provided the greatest amount of open dentinal tubules and lowest persistence of residues in the dentin (P <0.05). There were no differences between the other groups (P> 0.05). In Chapter 2...(Complete abstract electronic access below)

O objetivo do presente estudo foi comparar os efeitos de substâncias de limpeza (etanol a 95% ou xilol) e o momento do condicionamento ácido (imediato ou após 7 dias) na obtenção de túbulos dentinários abertos e avaliar a persistência de resíduos de um cimento à base de resina epóxi sobre a superfície dentinária. Além de, avaliar a capacidade de limpeza da superfície dentinária, impregnada por um cimento endodôntico à base de resina epóxi (AH Plus), proporcionada pelo etanol 95% ou pelo xilol e condicionamento ácido e seus efeitos sobre a interface dentina/sistema adesivo dentinário, por meio da avaliação da formação da camada híbrida e da resistência de união do sistema adesivo dentinário Scotchbond Universal (3M ESPE), imediatamente ou após 7 dias da limpeza dentinária e, da avaliação da formação da camada híbrida e da resistência de união do sistema adesivo dentinário Adper Scotchbond Multi Purpose (3M ESPE), imediatamente após a limpeza da superfície dentinária impregnada com o cimento. No capítulo 1, fragmentos de dentina de incisivos bovinos foram tratados com irrigantes endodônticos, impregnados com o cimento e divididos em 4 grupos (n=10): G1, etanol 95.0% - imediato; G2, xilol - imediato; G3, etanol 95.0% - após 7 dias e G4, xilol - após 7 dias. Após a obtenção das imagens em MEV, a contagem de túbulos dentinários abertos foi realizada com o programa Photoshop CS5. Outros 40 fragmentos foram preparados e analisados em MEV (500X), para a avaliação da persistência de resíduos do cimento endodôntico na dentina. A contagem dos túbulos dentinários abertos foi analisada com ANOVA e teste de Tukey (P=0,05) e a persistência de resíduos com os testes de Kruskal Wallis e Dunn (P=0,05). O protocolo de limpeza com o xilol e condicionamento ácido após 7 dias proporcionou maior quantidade de túbulos dentinários abertos e menor ...(Resumo completo, clicar acesso eletrônico abaixo)
Chemical removal protocols of endodontic sealer residues on dentin: influence on hybrid layer formation and bond strength to adhesive systems
Keywords: Dentina; Endodontia; Microscopia eletronica de varredura; Adesivos dentinários; Dentin; Endodontics; Scanning electron microscopy